Corporate social responsibility in the modern world-system - a case study of German Automobile Corporations’ social and environmental responsibilities in South Africa - Mossmann, Jannis (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science))--University of Stellenbosch, 2010.